SKAP interacts with Aurora B to guide end-on capture of spindle microtubules via phase separation. (23rd September 2021) - Zhang, Manjuan; Yang, Fengrui; Wang, Wenwen; Zohbi, Najdat; Wang, Xiwei; Wang, Dongmei; Zhuang, Xiaoxuan; Dou, Zhen; Liu, Dan; Song, Xiaoyu; Green, Hadiyah-Nicole; Liu, Xing; et al.
Abstract: Chromosome segregation in mitosis is orchestrated by the dynamic interactions between the kinetochore and spindle microtubules. Our recent studies show that mitotic motor CENP-E cooperates with SKAP and forms a link between kinetochore core MIS13 complex and spindle microtubule plus-ends to achieve accurate chromosome alignment in mitosis. However, it remains elusive how SKAP regulates kinetochore attachment from lateral association to end-on attachment during metaphase alignment. Here, we identify a novel interaction between Aurora B and SKAP that orchestrates accurate interaction between the kinetochore and dynamic spindle microtubules. Interestingly, SKAP spontaneously phase-separates in vitro via weak, multivalent interactions into droplets with fast internal dynamics. SKAP and Aurora B form heterogeneous coacervates in vitro, which recapitulate the dynamics and behavior of SKAP comets in vivo . Importantly, SKAP interaction with Aurora B via phase separation is essential for accurate chromosome segregation and alignment. Based on those findings, we reason that SKAP–Aurora B interaction via phase separation constitutes a dynamic pool of Aurora B activity during the lateral to end-on conversion of kinetochore–microtubule attachments to achieve faithful cell division.